Impact Evaluation of Cash and Food Transfers at Early Childhood Development Centers in Karamoja, Uganda: Endline Survey - International Food Policy Research Institute; United Nations International Children’s Emergency Fund; World Food Programme (International Food Policy Research Institute, 2016)
IFPRI in collaboration with UNICEF and WFP conducted a study of the effectiveness of food and cash transfers linked to participation in an Early Childhood Development (ECD) program in Uganda. This evaluation is part of a multicountry study to assess the relative impact of food and cash transfers on food security, nutrition, and other measures of human capital. The Uganda case study had two main objectives. First, it estimated the relative impact and cost-effectiveness of cash and food transfers on household food security. Second, it measured the impact and cost-effectiveness of cash or food transfers, joint with child participation in the ECD centers, on child development and nutrition. The Uganda ECD study was designed as a prospective, cluster-randomized control trial, in which treatment households would receive seven transfers of food or cash on approximately 6-week distribution cycles, conditional on having a child aged 3-5 years participating in an ECD center. The value of each transfer was 25,500 UGX (approximately $10.25) for both food and cash. The intervention started in April 2011, with a baseline survey conducted in Sep-Nov 2010 and an endline survey conducted in Mar-May 2012. The study used four survey instruments in each survey round: 1. Household questionnaire; 2. Child assessment and anthropometry; 3. ECD caregiver questionnaire; and 4. Community questionnaire. The household questionnaire collected detailed household-level information on socioeconomic characteristics and uses of resources, as well as individual-level information including ECD participation, education, and health. The child assessment and anthropometry questionnaire measured child development, anthropometric outcomes, and (only at endline) hemoglobin levels for selected children in the household. The ECD caregiver questionnaire collected information on characteristics of the ECD center’s primary caregiver, experiences running the ECD center, and the ECD center itself. The community questionnaire included information on socioeconomic and demographic characteristics of the community, its access to infrastructure, and a market survey.